1979
DOI: 10.1530/jrf.0.0550309
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of thymus weight, lumbar node weight and progesterone levels in syngeneically pergnant, allogeneically pregnant, and pseudopergnant mice

Abstract: Female CBA mice were mated to fertile CBA males, to vasectomized CBA males, to fertile C57BL males or to vasectomized C57BL males. After allogeneic or syngeneic mating the extent of thymic involution on the 10th day of pregnancy and pseudopregnancy was similar. Lumbar lymph node weight was not affected by pseudopregnancy but increased similarly in allogeneic and syngeneic pregnancies. Serum progesterone levels on the 10th day of pseudopregnancy were similar to those of non-pregnant females, and significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…66 Consistently, we observed a relative augmentation of Treg in thymus from normal pregnant mice compared to virgin ones, which was not detected in animals undergoing spontaneous abortion, 23 contrasting with data from Zhao and colleagues 26 that show no significant changes in the frequency of CD4 + CD25 + T cells in the thymus in both syngeneic and allogeneic mating combinations. Similar to what is observed in transplantation models where the lymph nodes draining the grafts show an enlargement shortly after transplantation, 67 there are reports demonstrating the increased weight of the uterine draining lymph nodes in pregnant animals in comparison with pseudopregnant or non-pregnant animals 57 while this could not be observed in mesenteric, axillary or inguinal lymph nodes. 62 Work from Chambers and Clarcke shows 57 a major increase in the lumbar lymph nodes of syngeneic mated mice.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…66 Consistently, we observed a relative augmentation of Treg in thymus from normal pregnant mice compared to virgin ones, which was not detected in animals undergoing spontaneous abortion, 23 contrasting with data from Zhao and colleagues 26 that show no significant changes in the frequency of CD4 + CD25 + T cells in the thymus in both syngeneic and allogeneic mating combinations. Similar to what is observed in transplantation models where the lymph nodes draining the grafts show an enlargement shortly after transplantation, 67 there are reports demonstrating the increased weight of the uterine draining lymph nodes in pregnant animals in comparison with pseudopregnant or non-pregnant animals 57 while this could not be observed in mesenteric, axillary or inguinal lymph nodes. 62 Work from Chambers and Clarcke shows 57 a major increase in the lumbar lymph nodes of syngeneic mated mice.…”
supporting
confidence: 71%
“…Similar to what is observed in transplantation models where the lymph nodes draining the grafts show an enlargement shortly after transplantation, 67 there are reports demonstrating the increased weight of the uterine draining lymph nodes in pregnant animals in comparison with pseudopregnant or non-pregnant animals 57 while this could not be observed in mesenteric, axillary or inguinal lymph nodes. 62 Work from Chambers and Clarcke shows 57 a major increase in the lumbar lymph nodes of syngeneic mated mice. In contrast, studies from Maroni and de Sousa 62 showed a higher increase in the draining lymph nodes of allogeneic matings in comparison with syngeneic ones.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…The interplay between hormonal and immunological factors contributes substantially to fetal tolerance. Pregnancy-associated hormones like the human chorionic gonadotropin (hCG), estrogen, and progesterone (P) increase during pregnancy and are essential for successful pregnancy outcome (1,2). hCG is a primate-specific hormone; that is, it is only produced by humans (3) and primates (4), and cannot be detected in rodents (5).…”
mentioning
confidence: 99%
“…Steroid hormones mainly estradiol (E2) and progesterone (P4) and gonadotropins mainly, the human chorionic gonadotropin (hCG) are essentially required for the establishment and maintenance of successful pregnancy [8,9]. These hormones sustain fetal tolerance by stimulating tolerance pathways and hampering detrimental immune responses through binding to their immune cell specific receptors and/or action via mediators.…”
Section: Pregnancy Hormones and Immune Suppressionmentioning
confidence: 99%